Long non-coding RNA CASC9 promotes the progression of retinoblastoma via interacting with miR-145-5p. Issue 18 (16th September 2020) - Zhang, Ting; Yang, Jingpu; Gong, Fangchao; Li, Lin; Li, Aipeng
ABSTRACT: Abnormal expression of long non-coding RNA cancer susceptibility candidate 9 (CASC9) has been found to play vital roles in many human tumors. However, the role and the regulatory mechanism of CASC9 have not yet been demonstrated in retinoblastoma (RB). Hence, we performed this study to explore the function and mechanism of CASC9 in RB. CASC9 expression was firstly detected in human RB tissues and cells. The influence of CASC9 on the malignant phenotypes of RB cells, including cell proliferation, invasion, epithelial–mesenchymal transition (EMT) and apoptosis, was analyzed by overexpressing or silencing CASC9. The association between CASC9, miR-145-5p and E2F transcription factor 3 (E2F3) was determined by dual-luciferase reporter assay and RNA immunoprecipitation. We found that CASC9 expression was elevated in RB tissues and cells. Overexpression of CASC9 significantly facilitated the proliferation, invasion and EMT of RB cells. On the contrary, knockdown of CASC9 inhibited the proliferation, invasion and EMT, while enhanced the apoptosis of RB cells. CASC9 acted as a competing endogenous RNA (ceRNA) for miR-145-5p to regulate E2F3. Additionally, miR-145-5p inhibitor and E2F3 overexpression both partly reversed the malignant phenotypes of RB cells affected by CASC9 knockdown. However, miR-145-5p overexpression further strengthened these features induced by CASC9 downregulation. These findings suggested that CASC9 contributed to RB development by regulating E2F3 via sponging miR-145-5p. CASC9 might be a possible therapeutic target for RB.